A matrix-based method for searching configurations of planetary gear trains. (February 2023) - Dong, Peng; Zuo, Shumiao; Liu, Tianyan; Xu, Xiangyang; Guo, Wei; Liu, Yanfang; Wu, Hongchao; Wang, Shuhan
Highlights: A matrix-based method is proposed to search configurations of planetary gear sets. Inherent and switchable connection matrix are defined for configuration structure. A detection method of mechanical structural interference is developed. Detection and optimization are conducted for desired transmission and step ratios. Valid configurations are obtained with little work and experience from engineers. Abstract: Better dynamic and economic performance of vehicles can be produced by increasing gears of the planetary gear trains (PGT), but a more complex structure would be required. Therefore, this paper proposes a matrix-based method for searching PGT configurations. Based on the basic connection matrix, the inherent connection matrix and switchable connection matrix are firstly established to describe the configuration structure. Then, the embedding process of shaft connection is simulated with three matrices for valid configurations, which have no mechanical structural interference. Finally, to achieve the desired transmission ratios and step ratios, detections are firstly conducted for the simple shift logic, and the optimization process of the stationary gear ratios is presented. Through this method, valid configurations can be obtained according to several design requirements without additional work from engineers. Besides, this method can also serve as a guide for both theoretical designs and practical applications of PGTs. Graphical abstract: Image, graphical abstract